Effects of music intervention on sleep quality of older adults: A systematic review and meta-analysis. (June 2021) - Wang, Cong; Li, Guichen; Zheng, Lufang; Meng, Xiangfei; Meng, Qiuyan; Wang, Shuo; Yin, Huiru; Chu, Jianfeng; Chen, Li
Highlights: Music interventions operate easily and can be promoted as effective strategies to improve the sleep quality of the elderly. Music interventions benefitted especially sleep latency, sleep duration, sleep efficiency and sleep of daytime dysfunction. The results indicated that music interventions might lead to a clinically important improvement in sleep quality of older adults. Abstract: Background: Music interventions have several benefits for sleep quality. However, the effects of music interventions on sleep quality in older adults are controversial. Objective: To summarize and evaluate the efficacy of music interventions on sleep quality in older adults. Methods: The Cochrane Library, Embase, PubMed, Web of Science and Chinese National Knowledge Infrastructure (CNKI) were systematically retrieved until June 2020, updated on March 13, 2021. Both experimental and quasi-experimental studies were included if they evaluated the efficacy of music interventions on sleep outcomes in older adults. The methodological quality was assessed by the Cochrane RoB 2.0 and ROBINS-I Tool. The random effects models and effect measure (MD) were adopted, and sensitivity analysis by omitting each study was conducted to explore the source of heterogeneity. Results: A total of 489 participants from 9 studies met the inclusion criteria. 6 studies were included in meta-analysis and sensitivity analysis, and 3 studies were included in the qualitative analysis. Main concerns about risk of bias were lack of blinding participants and investigators, and confounding factors might exist in non-RCTs. The Post-hoc meta-analysis indicated that music interventions might have a positive effect on sleep quality [MD = −2.64, 95 % CI (−3.76, −1.53), p  <  0.001; I 2  = 75.0 %]. Only one study evaluated adverse events and reported zero discomfort. Conclusions: The results indicated that music interventions might be beneficial for improving sleep quality, especially in sleep latency, sleep duration, sleep efficiency and sleep of daytime dysfunction in elderly individuals.